Programy kształcenia historyków w świetle Krajowych Ram Kwalifikacji - Wilczyński, Marek; Roszak, Stanisław (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2012)
In 2012 in Polish higher education a new curriculum was introduced. The new syllabuses are in accordance with the European Qualification Framework. This change means that previous teaching standards established by the Ministry of Education are about to disappear. The authors of the article present a review of the basic legal acts – European and Polish ones, which regulate changes. Stanisław Roszak and Marek Wilczyński show not only theoretical rules for building educational programs on the basis of learning outcomes, but also practical advice with reference to international patterns have been implemented. They point out possibilities created by the act concerning the construction of the new study courses for higher education. The analysis touches on the following aspects: the outcomes of teaching in the humanities (established by the Ministry), the outcomes of teaching in history departments (established by the faculties), the outcomes of the teaching of particular subjects (established by the academics). Besides the theoretical background to the construction of new programmes, specific practical solutions are included in the article, such as a syllabus for ancient history. The second part of the text is devoted to methods of managing and evaluating students’ learning. Methods of evaluation are crucial for a success of the reform. Evaluation is used not only to verify the knowledge and skills of the students. It should also be an important guide in helping to evaluate a teaching programme and the methods used by the teachers. Acquainting with the article will undoubtedly help developing new programs of educating the historians as a starting point for creative evolving of student’s centred learning educational model allowing further employability in changing market conditions.